Intimate partner violence during pregnancy: prevalence and associated factors - Ranielle de Paula Silva; Franciéle Marabotti Costa Leite (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE To identify the prevalence of violence during pregnancy and the association with the socioeconomic, behavioral and clinical characteristics of pregnant women. METHODS Cross-sectional study in a low-risk maternity hospital in the municipality of Cariacica, Espírito Santo. A total of 330 puerperal women were interviewed from August to October 2017. Information on socioeconomic, behavioral, reproductive and clinical characteristics, as well as life experiences, was collected through a questionnaire. To identify the types of violence, the proper World Health Organization instrument was used. Gross bivariate and multivariate analysis was performed and adjusted for Poisson regression with robust variance. RESULTS Prevalence was 16.1% (95%CI 2.5-20.4) for psychological violence, 7.6% (95%CI 5.1-11.0) for physical violence and 2.7% (95%CI 1.4-5.2) for sexual violence. Psychological violence remained associated with age, family income, beginning of sexual life, disease in pregnancy, desire to interrupt pregnancy and number of partners. Physical violence was associated with schooling, beginning of sexual life and disease in pregnancy. Sexual violence remained associated with marital status and desire to interrupt pregnancy (p < 0.05). CONCLUSIONS Psychological violence by an intimate partner was the most prevalent among pregnant women. Women that were younger, had lower income and less schooling, who started their sexual life before the age of 14 and who wished to interrupt pregnancy, experienced violence more frequently during pregnancy.